Reversing Morphine Induced Tolerance: Insights Into Cetirizine and Green Tea Extract Efficacy - Tahereh Eteraf-Oskouei, Phd; Adel Mahmoudi Gharehbaba, Phd; Solmaz Asnaashari, Phd; Zahra Fazli, Phd; Bohloul Habibi Asl, Phd (Current Therapeutic Research)
Background: The treatment of chronic pain presents a considerable difficulty, particularly due to opioid dependence, which is marked by tolerance and withdrawal symptoms. Opioids primarily target mu (μ) opioid receptors, providing pain relief while also leading to various side effects. This research aimed to examine the effectiveness of cetirizine and green tea hydroalcoholic extract (EXT) in altering morphine tolerance and improving analgesic effects. Methods: Adult male mice were divided into nine groups. In order to investigate the analgesic tolerance, animals received morphine on 14 consecutive days. Cetirizine (5, 10, 20 mg/kg, i.p.) and EXT (50, 100, 200 mg/kg, i.p.) were given before a test dose of morphine (9 mg/kg, i.p.). The analgesic effects were evaluated by the hot plate test. Results: Cetirizine with doses of 5, 10, 20 mg/kg, and 10 mg/kg showed a significant effect in reducing morphine tolerance 30 min (P < 0.0001) and 45 to 60 min (P < 0.0001) after test dose of morphine (9 mg/kg, i.p.) respectively. While the injection of different doses of the extract did not show any effect on tolerance to morphine. In the combined injection of these two drugs, there was no reduction in tolerance to morphine. Conclusions: Cetirizine but not EXT reversed morphine tolerance. Furthermore, the co-administration of cetirizine and EXT did not yield any significant benefits compared to the individual treatments.